Inflancka Travelogue: 10 Short Essays on “Decalogue” - Kickasola, Joseph G. (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Kieślowski scholar Joseph G. Kickasola documents his efforts to find and explore the Warsaw apartment complex where Krzysztof Kieślowski filmed his Decalogue series. His startling, unexpectedly emotional experience at such an ordinary place becomes an opportunity to reflect on the films, theorize on the function of place in them, and consider the way that human life and cinema feed into each other. Fictional stories and their cinematic constructions can deepen our experience, and make the world feel more lived in, more true. Nothing magical happened, but everything ordinary happened in all its fullness, like a kind of prophecy, fulfilled.